Variability in commercial histoplasma complement fixation antigens. - Leland, D S (1991)
Using Immuno-Mycologics (IMMY; Norman, Okla.) histoplasmal yeast (HY) and mycelial (HM) antibody complement fixation test antigens, we retested 1,386 samples that were initially tested with Meridian Diagnostics, Inc. (Cincinnati, Ohio), antigens. Histoplasma antibody was identified (greater than or equal to 1:16) in 20% of HY and 5% of HM samples reported to have titers of less than 1:8 with Meridian reagents. IMMY titers were at least fourfold higher than Meridian titers in 39% of HY and 54% of HM samples that initially had titers of greater than or equal to 1:8 with Meridian antigens. Because 30 of 58 (52%) samples from confirmed cases of histoplasmosis yielded negative results with Meridian antigens and positive results upon retesting with IMMY antigens, we concluded that the Meridian antigens had less reactivity with human histoplasmal antibody.